The contribution of emotional competence to organisational change in a Remote working settin - Tania Almeida; Célia Ribeiro; Paulo Pereira; Sofia Campos; António Ferreira; Clotilde Passos (Instituto Politécnico de Viseu, 2022)
Introduction: Organisations are constantly facing change and, over the last months, the COVID-19 pandemic has introduced a set of cross-cutting changes that forced many employees to work from home. Objectives: Identify the emotional competencies that can be found in the different organisational change processes related to remote working and to identify the relationship between emotional competencies and resistance to organisational change. Methods: This descriptive, quantitative, correlational study was conducted with a sample of 115 workers from different business sectors Results: Showed a correlation between cognitive rigidity and emotional competence. It also became evident that emotional competencies have no influence whatsoever on the change management processes that take place in a remote working environment. Conclusion: The respondents showed low resistance to change and high emotional competence, which may have helped them adapt to this kind of work.